On Green’s function for the Helmholtz equation in a wedge - Mel'nik, Yu. I.; Podlipenko, Yu. K. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
It is found that, in the spherical coordinate system, the fundamental solution of the Helmholtz equation in a wedge satisfies the Sommerfeld radiation conditions at infinity uniformly in angle coordinates.